METHODOLOGY FOR FABRICATION OF FORMING DENTURE WITH SILICONE BASE - Ivan Gerdzhikov (Peytchinski Publishing, 2018)
Introduction: The prosthetic treatment in patient with alveolar resorption is very difficult, and sometimes it is possible only after surgical preparation of the prosthetic field. In the cases, where surgical lift of the soft tissues in the vestibulum is performed, a forming denture, which has to shape the denture-bearing area, is required to design the healing of the soft tissues. Aim: The aim of the described method is to present the abilities of the forming dentures with silicone base, for conducting surgical preparation of prosthetic treatment in patients with resorption of the alveolar bone. Materials and methods: The prosthetic rehabilitation of 54-years-old female patient with complete edentulism and maxillary resorption, as a result of unsuccessful implant treatment with subperiosteal net, is described. After its surgical removal a complete dentures of the both jaws were made. The upper denture was used as a custom tray for taking impression with additive silicone, during the vestibuloplasty. The impression material was substituted with one-component heat-cured silicone Molloplast B in the dental laboratory and the denture was finished on the classical technology. After cleaning, polishing and disinfection , the denture was adjusted and articulated in patient's mouth. Results: The described methodology of prosthetic treatment and fabrication of forming denture allowed successful surgical treatment. The silicone base reduced the masticatory pressure and provided atraumatic conditions for the healing process. The vestibuloplasty ensured denture's retention and stability, which helped patient's chewing, feeding and speaking. Conclusion: The application of appropriate methodology and technique for fabrication of forming dentures provides successful design of the vestibulum and denture-bearing area. Тhis facilitates the conducting of the following prosthetic treatment.